2020
DOI: 10.3390/biom10020289
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin: Beyond the Endothelium

Abstract: Keywords: endoglin; CD105 TGF-β; BMP9; ALK-1; TRC105; tumor microenvironment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
59
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 149 publications
2
59
0
2
Order By: Relevance
“…Although initially studies on endoglin were focused on its role in endothelial cells and angiogenesis, early results provided data that showed endoglin expression on macrophages [ 11 ], leukocytes, syncytiotrophoblasts in the placenta [ 12 ] and fibroblasts in culture [ 13 ]. More recent work has revealed a crucial role for endoglin expression on other non-endothelial cells, which we have recently reviewed [ 14 ]. In both endothelial and non-endothelial cells, endoglin regulates TGF-β family member signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Although initially studies on endoglin were focused on its role in endothelial cells and angiogenesis, early results provided data that showed endoglin expression on macrophages [ 11 ], leukocytes, syncytiotrophoblasts in the placenta [ 12 ] and fibroblasts in culture [ 13 ]. More recent work has revealed a crucial role for endoglin expression on other non-endothelial cells, which we have recently reviewed [ 14 ]. In both endothelial and non-endothelial cells, endoglin regulates TGF-β family member signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, soluble endoglin is a circulating cleaved form of membrane endoglin, a transmembrane glycoprotein related to the function of vascular endothelium [ 18 ]. Soluble endoglin might represent an interesting biomarker of increased cholesterol levels since it was shown to be elevated in hypercholesterolemic [ 19 ] and FH patients [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…CD105 is a homodimeric transmembrane glycoprotein, and an auxiliary receptor of transforming growth factor-β (TGF-β), which binds to TGF-β1 and TGF-β3. It modulates TGF-β signaling by interacting with type I and type II TGF-β receptors, and activates a complex signaling pathway involving endothelial cell proliferation, migration and adhesion [10][11][12]. A recent meta-analysis on 30 studies involving 3,613 cancer patients found strong evidence of an increased CD105 expression in tumor microvessels correlating with poor overall survival, disease-free survival (DFS), and cancer-specific survival rates [10].…”
Section: Introductionmentioning
confidence: 99%